Analisa Keandalan Sistem Jaringan Distribusi 20 KV Dan Rekonfigurasi Recloser Pada Penyulang Kamal - Titiek Suheta; Muhammad Faisal A (Universitas Darul Ulum, 2022)
The increasing population in the Kamal area has improved the demand for electrical energy needs. Consequently, disruptions to the electricity distribution network may happen, such as blackouts in certain areas. The value of the reliability index will increase and not be in accordance with the standards that have been set. For this reason, this study calculated the reliability values of SAIFI and SAIDI on the Kamal feeder using the RIA (Reliability Index Assessment) method and the recloser reconfiguration using the fuzzy logic method. The simulation results indicated that the SAIFI value gained 6.331 times/year, while SAIDI obtained 20.212 hours/year. Based on recloser reconfiguration, the SAIFI value was earned 4.926 times/year, whereas SAIDI got 15.962 hours/year. The best location was located on line nineteen in group three, producing an output value of 0.461.